Microsurgery in Motion: An Objective Assessment of Microsurgical Skill and Efficiency - Lyon, Sarah M.; Zeng, Weifeng; Yang, Su; Wise, Brett J.; Mohamadipanah, Hossein; Pugh, Carla M.; Poore, Samuel O. (Journal of Reconstructive Microsurgery, 2025)
High levels of precision, as well as controlled, efficient motions, are important components of microsurgical technique and success. An accurate and objective means of skill assessment is lacking in resident microsurgical education. Here we employ three-dimensional, real-time motion-tracking technology to analyze hand and instrument motion during microsurgical anastomoses. We hypothesize that motion metrics can objectively quantify microsurgical skill and predict the overall level of expertise.Seventeen participants including medical students, plastic surgery residents, and attendings performed two end-to-end arterial microsurgical anastomoses in a laboratory setting. Motion tracking sensors were applied to standardized positions on participants' hands and microsurgical instruments. Motion and time parameters were abstracted using sensor-derived position data.A total of 32 anastomoses were completed and analyzed. There were significant differences in time for task completion and idle time between attendings and junior residents (post-graduate year (PGY)1–3). Path length and working volume consistently differentiated between students and attendings for all phases of an anastomosis. Motion and time data were less able to consistently distinguish attendings from residents stratified by laboratory anastomosis experience.Quantifiable motion parameters provide objective data regarding the efficiency of microsurgical techniques in surgical trainees. These data provide a basis for microsurgical competency assessments and may inform future structured feedback through instruction, instruments, and technological interfaces.
Keywords: microsurgery; education; motion tracking; simulation